Identification and characterization of the nitrifying microorganisms in a temperate beech forest and in enrichment cultures originating from hot springs at Lake Baikal and Kamchatka - Hauzmayer, Sandra (2010)
Bakterien und Archaeen sind die hauptverantwortlichen Organismen für Nitrifikation, einem Schlüsselprozess im globalen Stickstoffkreislauf und können in fast allen Habitaten der Welt gefunden werden können. In dieser Studie wurden die nitrifizierenden Mikroorganismen zweier sehr unterschiedliche Habitate untersucht. Zum einen handelte es sich um Anreicherungen, die von heißen Quellen des Baikalsees (Russland) und Kamchatka (Russland) stammen, zum anderen um Boden- und Laubstreuproben (Bodenhorizonte L und F) eines temperaten, sauren Waldstandortes. Die Ammoniak- und Nitrit-oxidierenden Mikroorganismen, der aus heißen Quellen stammenden, bei 46°C wachsenden Anreicherungen, wurden mittels Amplifizierung und Klonierung diverser molekularer Marker (16S rDNA, AmoA, NxrB) untersucht. Daraufhin wurden für diese Mikroorganismen spezifische Sonden entwickelt und die Mikroorganismen mittels FISH detektiert. Nitrit-oxidierende Mikroorganismen aus Anreicherung 8 wurden zusätzlich mittels Immunofluoreszenz-Technik auf die aktive Expression des, für Nitrit Oxidation verantwortlichen Enzyms, Nitritoxidoreduktase (NXR) hin untersucht und mittels Fluoreszenz In Situ Hybridisierung in Kombination mit Mikroautoradiographie auch funktionell getestet. Durch Amplifizierung und Klonierung von 16SrDNA und amoA Genen, konnten die Ammoniak-oxidizerenden Mikroorganismen als zum Phylum der Crenarchaeota zugehörig identifiziert werden. Phylogenetische Analyse der Sequenzen zeigte, dass die Organismen in eine Gruppe unkultivierter Crenarchaeoten fallen, die zwischen der so genannten „marine group I.1a“ und der „SAGMGC-1 group“ liegt. Diese Gruppe von Crenarchaeoten konnte zuvor noch nicht mit Ammoniak-Oxidation in Verbindung gebracht werden. Die Nitrit-oxidizerenden Mikroorganismen konnten als Nitrospira-ähnliche Bakterien identifiziert werden, die aktiv das Enzym Nitritoxidoreduktase exprimierten und bei einer Temperatur von 43°C mit Nitrit als alleiniger Energiequelle aktiv Stoffwechsel betrieben. Die nitrifizierenden Mikroorganismen eines temperaten sauren Waldstandortes wurden ebenfalls mittels Amplifizierung und Klonierung phylogenetischer und funktioneller Markergene charakterisiert. Im Gegensatz zu anderen Studien war es nicht möglich Gene bekannter Nitrifikanten aus den Laubstreuhorizonten zu amplifizieren. Dieses Ergebnis deutet darauf hin dass die Nitrifikation in diesen Horizonten möglicherweise hauptsächlich von heterotrophen Nitrifizierern durchgeführt wird. Für Horizont A war es hingegen möglich Gene aller terrestrisch vorkommenden Nitrifizierer zu detektieren. Für Ammoniak-oxidizerende Archaeen und Nitrospira-ähnlichen Bakterien wurde außerdem auch Diversität innerhalb der phylogenetischen Gruppen festgestellt, was auf eine hohe Diversität nitrifizierender Mikroorganismen in diesem Bodenökosystem hinweist. Es darf natürlich trotzdem nicht vergessen werden dass alle Daten aus Klonbibliotheken stammen, weshalb keinerlei Aussagen über Häufigkeit, Aktivität oder Beitrag zum Stickstoffkreislauf getroffen werden können. Für die Erforschung Nitrospira-ähnlicher Bakterien, wurde das nxrB Gen, das die beta-Untereinheit der Nitritoxidoreduktase kodiert, hinsichtlich der Eignung als zusätzlicher molekularer Marker evaluiert. Es wurde eine Datenbank klonierter und sequenzierter nxrB Gene von verfügbaren Kulturen, Anreicherungen und aus Umweltproben erstellt. Phylogenetische Analyse der Sequenzen zeigte, dass die 16SrDNA und nxrB basierte Phylogenie Nitrospira-ähnlicher Bakterien zu einem hohen Grad kongruent ist und es keinerlei Hinweise auf lateralen Gen Transfer gibt. Dementsprechend könnte nxrB ein passender funktioneller Marker für die phylogenetische Analyse Nitrospira-ähnlicher Bakterien sein. Nitrification, a key process in the global nitrogen cycling, is mainly mediated by nitrifying microorganisms that can be discovered in nearly every habitat around the world. In this study nitrifying enrichment cultures originating from two hot springs at Lake Baikal (Russia) and Kamchatka (Russia) and nitrifying microorganisms in soil and leaf-litter (soil horizons L and F) of a temperate acidic forest site were investigated. The phylogeny of AOO and NOB, metabolizing NH3 (enrichment culture 8) or NO2- (enrichment cultures A, Ca and 4) to NO3- in the enrichment cultures, isolated from the hot springs and growing at 46°C, was analyzed via amplification, cloning and sequencing of diverse molecular markers. Subsequently, FISH with probes specific for the detected microorganisms was applied for in situ detection and the NOB were additionally characterized functionally by application of immunofluorescence, targeting the nitrite oxidoreductase (NXR), and FISH-MAR. Thereby, the AOO thriving in enrichment culture 8 could be identified as crenarchaeotes. Phylogenetic analysis showed that they are affiliated with an uncultivated lineage of crenarchaeotes, in between marine group I.1a and SAGMGC-1, which hadn’t been linked to ammonia oxidation yet. The dominant NOB could be confirmed as a novel sublineage of Nitrospira-like bacteria that were actively expressing the NXR, the enzyme catalyzing nitrite oxidation, as could be shown by immunofluorescence and actively metabolizing at 43°C in the presence of NO2- as the sole energy source. The nitrifying community at a temperate acidic forest site was also assessed by amplification and cloning of phylogenetic and functional marker genes. Contrary to available literature, it was not possible to amplify any gene linked to known nitrifiers from leaf-litter layers, suggesting that nitrification is mainly mediated by heterotrophic microorganisms. However, genes of all known nitrifiers common in terrestrial habitats could be detected in soil horizon A (soil). For AOA and Nitrospira spp. additional diversity within these phylogenetic groups was observed, pointing towards a high diversity of nitrifiers within this soil ecosystem. Nevertheless, no conclusions about the abundance or their respective contribution to the nitrogen cycling, thus about the key players in this environment, can be drawn, since the data obtained simply rely on clone libraries. For the investigation of Nitrospira-like bacteria nxrB, the gene encoding the beta-subunit of the NXR, was assessed for the use as an additional molecular marker. Therefore a database from cloned and sequenced nxrB genes of available cultures, enrichment cultures and environmental samples was established. Phylogenetic analysis showed that 16S rRNA gene and nxrB based phylogeny of Nitrospira-like bacteria is congruent to a high degree, without any evidence for HGT. Therefore, nxrB is suggested to be a suitable functional marker for the phylogenetic analysis of Nitrospira-like bacteria. Molecular techniques nowadays not only provide great insight into the constitution of microbial communities in an environment but also allow statements about their activities. Nevertheless, the actual isolation of microorganisms, to gain detailed insight into the physiological capabilities and regulation mechanisms of organisms, remains as important as ever. Therefore here, investigating two different environments, not only a small window into the nitrifying community in an acidic forest soil, but also a first identification of several NOB and probably a new lineage of AOA was presented. Furthermore, members of a new sublineage of the previously identified thermophilic Nitrospira-like bacteria, growing at a temperature of 46°C, were shown to be active under nitrifying conditions. Altogether these results are shed further light on the phylogenetic and physiological diversity of nitrifying microorganisms.